Investigating the Feasibility, Acceptability and Efficacy of Using Modified-Written Exposure Therapy in the Aftermath of a Terrorist Attack on Symptoms of Posttraumatic Stress Disorder Among Afghan Adolescent Girls - Ahmadi, Sayed Jafar; Musavi, Zeinab; Samim, Nasratullah; Sadeqi, Masooma; Jobson, Laura (Frontiers in Psychiatry, 2022)
Background: The aim of this study was to assess the efficacy, acceptability and feasibility of using modified written exposure therapy (m-WET) to treat symptoms of posttraumatic stress disorder (PTSD) in Afghan adolescent girls in the aftermath of a terrorist attack. Methods: 120 Afghan (Hazara) adolescent girls who had been exposed to the Sayed al-Shuhada school terrorist attack were randomly assigned to the m-WET (n= 40), trauma-focused cognitive behavior therapy (TF-CBT) (n = 40), or control groups (n = 40). m-WET involved five consecutive daily group sessions where participants simply wrote about the terrorist attack including thoughts and feelings. TF-CBT was an intensive five-session group intervention. The control group had no additional contact. The trial was undertaken at a local non-government organization in Kabul. The primary analysis was comparing PTSD symptoms (Child Revised Impact of Event Scale-13) in the three groups at post-intervention and three-month follow-up. Results: Overall, participant and facilitator satisfaction with m-WET was high. Acceptability of m-WET was relatively high, with 15% drop-out in the m-WET group and all m-WET sessions were attended. While the groups did not differ significantly in PTSD symptoms at baseline, the m-WET group had significantly lower levels of PTSD symptoms compared to the control group at post-intervention and follow-up. There was no significant difference between the m-WET and TF-CBT groups. Conclusions: The findings suggest m-WET may be promising intervention for the treatment of PTSD among adolescent girls in humanitarian settings. Further research in the area is warranted.